O uso e ocupação da terra e as águas subterrâneas: análise do perigo de contaminação, aplicando os métodos GOD e POSH no Aquífero Tubarão, município de Itu / SP - Fritzen, Moacir (2023)
The exploitation of groundwater in Brazil ensures water security for millions of people and the various residues discarded by man, coupled with lack of proper planning, have been compromising the quality of these waters. The respective work analyzed the society-nature relationship according to the use and occupation of the land and its impacts on the quality of the groundwater. The study area was delimited by the portion of the Tubarão Aquifer situated in the Municipality of Itu / SP. The city suffers with constant hydric crises and the underground water becomes an important resource for the complementation of the public supply. Regarding the methodological aspects, it was accomplished firstly a bibliographical revision in the intention of having a safe base on the thematic that involves the underground water dynamics, as well as aspects that involve or affect its quality. The GOD method was also used to analyze the natural vulnerability of the aquifer and the POSH method was used to analyze the potential contaminant loads, diffuse or punctual, in the study area. Subsequently, a study of the contamination danger to the Tubarão Aquifer in Itu / SP was carried out, starting with the land use and occupation analysis, with the making of the map of the potential contaminant loads, in superposition to the natural vulnerability map of the aquifer, thus defining the respective danger levels for the studied area. Field observations were made in order to empirically verify the danger areas of contamination, relevant to the present study. With the application of the methods and relevant analyses, the natural vulnerability was classified as low to high vulnerability, the potential contaminant loads were classified as low to high, and the hazard levels of contamination ranged from very low to high. The factors that influenced these results were also identified, thus identifying the human activities with the highest probability of negative impacts on the aquifer.